Sistem Otentifikasi Otomatis Kendala Perangkat Jaringan Menggunakan NDLC - Muhammad Fawazi Hadi; Viviana Herlita Vidiasari; Christoper Michael Lauwl; Husain Husain; Farda Milanda Amin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The authentication system is a monitoring system where if there is a network problem, it can provide information quickly. The research was conducted at Bumigora University, using 3 buildings as research materials implemented in the form of topology design. The monitoring is carried out to anticipate lost connections or network disconnections caused by certain factors. The Network Development Life Cycle (NDLC) method is the appropriate method for conducting this analysis, because it focuses on parameters such as network reliability and the ability to secure data transmission. The stages of the NDLC method consist of analysis, design, simulation prototype, implementation, monitoring and management, but in this study the author only used 3 stages, namely analysis, design, simulation prototype and implementation. The NDLC method has been proven to increase network security and reliability, as well as minimize downtime due to device failure or disconnection of data transmission. Automatic authentication implemented through NDLC allows real-time device monitoring, by connecting the API with telegram. Telegram will provide notifications in the form of network condition statuses that are experiencing problems. So that the IT team can control the condition of network devices through telegram notifications. This can facilitate network management and efficiency of checking time in maintaining the stability and performance of the network as a whole.